Low intensity cycle ergometer exercise improve balance in breast cancer women underwent chemotherapy - Juraita; Andriati; Dyah Intania Sari; Desak Gede Agung Suprabawati; Mahmudah (Physical Therapy Journal of Indonesia, 2026)
Background: Breast cancer is the most common type of malignancy affecting women and principal cause of cancer-associated deaths. Chemotherapy often induces side effects such as fatigue, neuropathy, and muscle weakness, which contribute to impaired balance and increased fall risk. This study aimed to investigate the impact of low-intensity cycle ergometer exercise on balance performance in breast cancer women underwent chemotherapy. Methods: Randomized controlled trial with pretest–posttest design was conducted. Twenty-two eligible participants (aged 18–59 years, stage II–III breast cancer) were randomly assigned to treatment group (low-intensity cycling plus breathing exercises) or control group (breathing exercises only) for eight weeks. Balance was assessed using the Single Leg Stance (SLS) test, Short Physical Performance Battery (SPPB), and Activity-Specific Balance Confidence (ABC) scale. Data were analyzed using paired and independent t-tests or their non-parametric equivalents with a significance level of p < 0.05. Results: The treatment group showed significant improvements in SLS (p < 0.001, d = 3.67), SPPB (p = 0.003, d = 0.475), and ABC scores (p = 0.006, d = 0.934). No significant differences were observed in the control group. Conclusion: Low-intensity cycle ergometer exercise effectively enhances static and dynamic balance, functional performance, and confidence in women with breast cancer during chemotherapy, suggesting its suitability as a safe and beneficial component of rehabilitation protocols.